Application of RBV Theory In Measuring The Success of MSME Competitive Advantage Business Strategies In The Era of Uncertainty - Efrina S, Liona; Azmi, Mohamad; Primadiva, Parassela Pangestu; Utama, Ahmad Nur Budi; Anggun, Debby (SAINTIS Publishing, 2024)
The application of Resource-Based View (RBV) theory becomes relevant for MSMEs to maximize internal resources that are unique and difficult to imitate in order to create a sustainable competitive advantage. The purpose of this study is to provide a more comprehensive insight into the role of a combination of internal resources and digital strategies in creating a sustainable competitive advantage amid market uncertainty.This research uses a quantitative method with a case study approach to gain a deeper understanding of the phenomenon in a particular context. Data collection techniques were conducted through questionnaires, observations, interviews, and documentation including reports, guidelines, and related research journals. After the data was collected, the analysis was carried out quantitatively using SEM-PLS.The results concluded that social capital, quality products, owner dedication, qualified staff, and effective control influence the success of MSMEs in a changing market.The application of Resource-Based View (RBV) theory emphasizes the importance of utilizing internal and external resources to create competitive advantage. In an era of uncertainty, the utilization of these resources allows MSMEs to adapt and survive in a dynamic market.